A política negativa em Adorno: Possibilidade de uma vida emancipada - Pies, Neri (Universidade do Vale do Rio dos Sinos, 2017)
The following thesis aims to thematize the possibility of a Negative Politics in Adorno in order to think about the emancipated life. The disenchantment process of the enlightenment world, that promised freedom, scientific certainty and progress, transformed reason into a tool of domination and masked the reality, establishing, a managed system. This structure caused the narrowing of critical rationality and eliminated the tension between concept and reality. It also hid the real politics, because the managed system does not consider the singularities, the non identical, something that appears contradictory in human life and in society. In this way, the objective of politics is covered, it becomes an abstract concept, at the service of the instrumental bourgeois system. The real politics is more than what immediately appears in the totality of the managed society, thats's why, our objective is to make an exercise, in the works of Theodor Adorno, the structure that apprehends and directs the politics understanding how this positioning takes the individual and the society to the decay. But also, we intend, from Adorno thoughts, point out some perspectives that can lead humanity and society to emancipatory processes which, following the terminology of Adorno, we call negative politics. To find the perspectives, we believe that it is necessary to take the bark around politics, to expose the reality in which it is inserted and to give dynamicity so that the heterogeneous could live. In this sense the question remains: could this be done through the dynamics of negative dialectics? In Adorno's theory, the dialectic is not complete, it stops at the moment of negativity, articulating and intending the reason permanently as the reflexivity occurs, the reason illuminates and qualifies reality without making it an abstract concept, the elements crystallize by an objective movement projecting new constellations. This dynamics, of negative dialectics, can envisage, articulate and illuminate politics, bringing the emancipatory possibilities of life and a better society without making it administered. This research analyzes can negative politics erase the ideological layer that hides contradictions and bring out a new configuration, another reality, or a real reality. It also compromises san a negative policy keep a tension, a force field, and can it go beyond the immediate surface of things by not being content with appearances, can it resist and oppose the bourgeois structure and the falsity of the whole by the truth. With these open questions, we challenge ourselves to construct a reflection in the books of Theodor Adorno, through negative politics, believing, that there is no teleology of society and no rationality of events previously fixed.
Keywords: Adorno; Dialética negativa; Esclarecimento; Política negativa; Teoria crítica; Vida emancipada; Adorno; Negative dialectics; Clarification; Negative politics; Critical theory; Emancipated life; ACCNPQ::Ciências Humanas::Filosofia